A INFLUÊNCIA DA QUALIDADE DA VOGAL NA DETERMINAÇÃO DO PESO SILÁBICO E FORMAÇÃO DOS PÉS: O ACENTO PRIMÁRIO DO PORTUGUÊS - Bonilha, Giovana (Organon, 2004)
This paper addresses primary stress in Brazilian Portuguese considering the sonority ofvowels for the construction of feet. In our proposal, in words, as saci and urubu for example, primarystress foot is iambic because [i] and [u], when positioned at the end of a prosodic word, are consideredgood peak elements. A constraint against the positioning of i/u in the weak part of the foot, *T/i,u,ranked higher in the hierarchy, can explain how a trochaic language, like Brazilian Portuguese, canpresent iambic feet in some words.